INTERNATIONAL FOOD REGIME - A. V. Malov (MGIMO University Press, 2018)
The review article reveals the content of the concept of Food Regime, which is little-known in the Russian academic reference. The author monitored and codified the semantic dynamic of the terminological unit from its original interpretations to modern formulations based on the retrospective analysis. The rehabilitation of the academic merits of D. Puchala and R. Hopkins — authors who used the concept Food Regime for a few years before its universally recognized origin and official scientific debut, was accomplished with help of historical and comparative methods. The author implemented the method of ascension from the abstract to the concrete to demonstrating the classification of Food Regimes compiled on the basis of geopolitical interests in the sphere of international production, consumption, and distribution of foodstuffs. The characteristic features of historically formed Food Regime were described in the chronological order, as well as modern tendencies possessing reformist potential were identified. In particular, it has been established that the idea of Food Sovereignty (which is an alternative to the modern Corporate Food Regime) is the subject for acute academic disputes. The discussion between P. McMichael P. and H. Bernstein devoted to the “peasant question” — mobilization frame of the Food Sovereignty strategy was analyzed using the secondary data processing method. Due to the critical analysis, the author comes to the conclusion that it is necessary to follow the principles of the Food Sovereignty strategy to prevent the catastrophic prospects associated with ecosystem degradation, accelerated erosion of soils, the complete disappearance of biodiversity and corporate autoc racy successfully. The author is convinced that the idea of Food Sovereignty can ward off energetic liberalization of nature, intensive privatization of life and rapid monetization of unconditioned human reflexes.